Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ece3.2665
|View full text |Cite
|
Sign up to set email alerts
|

Islands within an island: Population genetic structure of the endemic Sardinian newt,Euproctus platycephalus

Abstract: The identification of historic and contemporary barriers to dispersal is central to the conservation of endangered amphibians, but may be hindered by their complex life history and elusive nature. The complementary information generated by mitochondrial (mtDNA) and microsatellite markers generates a valuable tool in elucidating population structure and the impact of habitat fragmentation. We applied this approach to the study of an endangered montane newt, Euproctus platycephalus. Endemic to the Mediterranean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 174 publications
(187 reference statements)
1
4
0
Order By: Relevance
“…arnoldi (weighted average Ar = 3.398 and H E = 0.441)[ 26 ]. These values are also consistent compared to other mountain brook newts, such as Euproctus platycephalus on Sardinia (weighted average Ar = 2.376 and H E = 0.6 [ 65 ]) and are within the typical range of other urodeles and temperate amphibians (0.4–0.6; [ 66 ] and references therein). In accordance with other Pyrenean species, such as the Ericaceae Rhododendron ferrugineum [ 8 ], we found that genetic diversity of C .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…arnoldi (weighted average Ar = 3.398 and H E = 0.441)[ 26 ]. These values are also consistent compared to other mountain brook newts, such as Euproctus platycephalus on Sardinia (weighted average Ar = 2.376 and H E = 0.6 [ 65 ]) and are within the typical range of other urodeles and temperate amphibians (0.4–0.6; [ 66 ] and references therein). In accordance with other Pyrenean species, such as the Ericaceae Rhododendron ferrugineum [ 8 ], we found that genetic diversity of C .…”
Section: Discussionsupporting
confidence: 82%
“…In some species there is no correlation found between the altitudinal gradient and the population differentiation or genetic diversity (e.g. Rana chensinensis [ 69 ]; Euproctus platycephalus [ 65 ]). In other species, the genetic diversity is negatively correlated with altitude (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population decline and extinction threaten amphibians due to habitat loss, climate change, pollution, and disease [77]. Conservation genetics focuses on genetic diversity, population structure, and gene flow in amphibians [78], while population ecology studies statistical processes regulating populations, such as birth rates, death rates, and interpopulation movement [79]. Research in these areas also involves genetic resource management, hormone induction in breeding systems, and suitable habitat models (Figure 4b).…”
Section: Conservation Genetics and Population Ecology Of Amphibiansmentioning
confidence: 99%
“…As exothermic vertebrates dependent on both terrestrial and aquatic environments, amphibians are particularly susceptible to changes in the environment (Araújo et al, 2008;Mushet, Euliss, Chen, & Stockwell, 2013;Zeisset & Beebee, 2008). The signatures of past climate change are present in the genetic structure of many amphibian species (Ball et al, 2017;Lee-Yaw, Irwin, & Green, 2008;Wielstra et al, 2013;Zeisset & Beebee, 2008;Zhou et al, 2017), and understanding how ancient climates affected current population structure can provide key insights into predicting how future climate change might impact amphibian populations.…”
Section: Introductionmentioning
confidence: 99%